2000
DOI: 10.1007/s004250000323
|View full text |Cite
|
Sign up to set email alerts
|

Differential activation of H + -ATPase genes by an arbuscular mycorrhizal fungus in root cells of transgenic tobacco

Abstract: In arbuscular mycorrhizas, H+-ATPase is active in the plant membrane around arbuscules but absent from plant mutants defective in arbuscule development (Gianinazzi-Pearson et al. 1995, Can J Bot 73: S526-S532). The proton-pumping H+-ATPase is encoded by a family of genes in plants. Immunocytochemical studies and promoter-gusA fusion assays were performed in transgenic tobacco (Nicotiana tabacum L.) to determine whether the periarbuscular enzyme activity results from de-novo activation of plant genes by an arbu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
69
0
5

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(78 citation statements)
references
References 22 publications
4
69
0
5
Order By: Relevance
“…We suggest that, together with the protons, which are actively transported into the interfacial apoplast by the plant and also by fungal H + -ATPases (Murphy et al, 1997;Gianinazzi-Pearson et al, 2000;Krajinski et al, 2002;Requena et al, 2003;Balestrini et al, 2007), the protons coming from the NH 4 + deprotonation process remain in the interface space and maintain or even reinforce the gradient for H + -dependent transport processes (Fig. 9).…”
Section: Ammonium and Phosphate Uptake At The Interface: A Speculativmentioning
confidence: 98%
“…We suggest that, together with the protons, which are actively transported into the interfacial apoplast by the plant and also by fungal H + -ATPases (Murphy et al, 1997;Gianinazzi-Pearson et al, 2000;Krajinski et al, 2002;Requena et al, 2003;Balestrini et al, 2007), the protons coming from the NH 4 + deprotonation process remain in the interface space and maintain or even reinforce the gradient for H + -dependent transport processes (Fig. 9).…”
Section: Ammonium and Phosphate Uptake At The Interface: A Speculativmentioning
confidence: 98%
“…In barley (Hordeum vulgare), Murphy et al (1997) described the first plant H ϩ -ATPase to be differentially expressed in response to mycorrhizal colonization. More recently, at least two H ϩ -ATPase isoforms have been identified in the interaction of mycorrhizal fungi and tobacco (Nicotiana tabacum; Gianinazzi-Pearson et al, 2000). By using ␤-glucuronidase-fused promoter constructs, these authors showed induction of these two isoforms in arbuscule-containing cells.…”
mentioning
confidence: 99%
“…A estimulação da atividade ATPásica verificada no presente estudo (Figura 2a) está em concordância com dados moleculares que relatam a capacidade do FMA em induzir a expressão de genes de H + -ATPases de membrana plasmática da planta hospedeira (Murphy et al, 1997;Gianinazzi-Pearson et al, 2000), mais especificamente identificada na membrana periarbuscular (Krajinski et al, 2002). A menor taxa de estimulação da atividade ATPásica 20 dias após o plantio pode estar correlacionada com o fato de que, neste estádio inicial da colonização, a área da raiz que apresenta arbúsculos é muito incipiente, comparada à ocorrência verificada aos 60 dias, estádio no qual tem sido observada a maior proliferação de arbúsculos na cultura do milho colonizada com FMAs do gênero Glomus (Alexander et al, 1989;Toth et al, 1990).…”
Section: Resultsunclassified
“…O desempenho inferior de Gm, no que tange à ativação das ATPases e PPases, pode estar relacionado com características da espécie que não forma vesículas e apresenta um tipo de colonização anatomicamente diferente de Gc, com hifas intercelulares mais esparsas e com uma menor freqüência de arbúsculos (Smith & Read, 1997). Dada a importância dessas estruturas no processo de troca bidirecional e na ativação de genes relacionados com à H + -ATPases de células corticais (Murphy et al, 1997;Gianinazzi-Pearson et al, 2000), pode-se esperar que o Gm seja menos efetivo em desencadear respostas na atividade das ATPases e PPases. Plantas inoculadas com Gc apresentaram concentrações de nutrientes (exceto N) e medidas de crescimento (exceto matéria fresca da parte aérea) superiores àquelas inoculadas com Gm que, todavia, apresentaram valores superiores aos obtidos com plantas não inoculadas, com exceção no conteúdo de Ca e matéria fresca da parte aérea (Quadro 1).…”
Section: Resultsunclassified
See 1 more Smart Citation